Was Keynes right? A reconsideration of the effect of a protective tariff under stagnation - Ken'ichi Hashimoto; Kazuyuki Miyagiwa; Yoshiyasu Ono; Matthias Schlegl (Osaka University, Institute of Social and Economic Research (ISER), 2024)
This paper first presents a dynamic model that features both real and monetary aspects of international trade and is capable of dealing with both full employment and secular unemployment. The model is then utilized to examine the effect of a tariff on the terms of trade, the trade pattern, real consumption and employment of labor. It is shown that with full employment in both countries, a tariff by the home country improves its terms of trade and increases its national welfare at the expense of the foreign country. These results however are reversed in the presence of unemployment in both countries. We also examine the asymmetric cases and calibrate our model to evaluate numerically the effect of large tariff changes. The main finding is that the tariff only worsens the economy when it is already stagnant.
Keywords: E24; E31; F13; F41; J20; 330; demand shortage; unemployment; tariffs; secular stagnation